Corynebacterium Bone and Joint Infection (BJI): A Retrospective Cohort Study in a Reference Center for BJI Management - Tristan Ferry; Pierre Chauvelot; Claire Triffault-Fillit; Evelyne Braun; Thomas Perpoint; Frederic Laurent; Michel-Henri Fessy; Sébastien Lustig; Christian Chidiac; Florent Valour (Open Forum Infectious Diseases, 2017)
Abstract Background Corynebacterium is a rare etiologic agent of BJI. We aimed to describe this rare clinical condition and to assess treatment failure determinants. Methods All adult patients with proven Corynebacterium BJI (i.e., consistent clinical/radiological signs, AND ≥2 reliable positive bacteriological samples, AND treated as such) were included in a retrospective cohort study. After cohort description, determinants of treatment failure (i.e., infection persistence, relapse, requirement of additional surgical procedure, and BJI-related death) were determined using stepwise logistic regression and Kaplan-–Meier curve analysis. Results The 51 included BJI were more frequently chronic (88.2%), orthopaedic device related (ODI, 74.5%) and polymicrobial (78.4%). Surgery was performed in 92.2% of cases, and considered as appropriate in 76.5% of them. The main first-line antimicrobials were glycopeptides (68.6%), β-lactams (50%), and/or clindamycin (10.0%). Three (5.9%) patients received daptomycin as part of first-line regimen, and 8 (15.7%) at any point of treatment. After a follow-up of 60.7 (IQR 30.1–115.1) weeks, 20 (39.2%) treatment failures were observed, including 4 (20%) Corynebacterium-documented relapse. Independent risk factors were initial biological inflammatory syndrome (OR 16.1; P = 0,030) and inappropriate surgical management (OR 7.481; P = 0.036). Interestingly, all patients receiving daptomycin as part of first-line regimen failed (P < 0.001), including one patient with a Corynebacterium-documented relapse with a daptomycin increased MIC. Among patients with ODI, survival curve analysis disclosed a worst prognosis in case of prosthetic joint infection (P = 0.030), unappropriate surgical management (P = 0.029) and daptomycin use as first-line regimen (P < 0.001). Conclusion Corynebacterium BJI is a poorly known condition, frequently chronic, and polymicrobial. An important rate of failure was observed, associated with inappropriate surgical management and daptomycin use as part of first-line regimen. As described for other clinical conditions such as infective endocarditis, daptomycin should be avoid or used in combination therapy to prevent resistance selection and treatment failure. Disclosures T. Ferry, HERAEUS: Consultant, Speaker honorarium. S. Lustig, Heraeus: Consultant, Consulting fee